Digital Transformation in Supporting Accounting Automation in the Industrial Bank Iraq - Ahmed Neamah Abed; Faris Abdulzahra Abdulhussin Alkhalidy; Jinan Abed Khaji; Anmar Adnan Khudhair; Ahmed Obayes Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital transformation is fundamentally reshaping accounting practices globally through technologies including artificial intelligence, automation, blockchain, and big data analytics. Specific Background: The Iraqi banking sector continues to rely on traditional manual processes and paper-based documentation, resulting in increased operational costs, effort, and time inefficiencies that hinder competitive performance. Knowledge Gap: While previous research has documented digital transformation's benefits in accounting, limited empirical evidence exists examining its specific impact on accounting automation within industrial banks in developing economies like Iraq. Aims: This study investigates how digital transformation contributes to enhancing accounting automation levels in the Industrial Bank Iraq, examining the relationships between digital transformation implementation, accounting practices, and automation outcomes. Results: Analysis of 42 accountants and auditors revealed a strong positive correlation (R=0.932) between digital transformation and accounting automation, with digital transformation explaining 86.9% of variance in accounting practices and automation performance, supporting both hypothesized relationships. Novelty: This research provides context-specific empirical evidence from Iraq's industrial banking sector, demonstrating quantifiable impacts of digital transformation on accounting automation in a transitioning economy. Implications: Findings suggest that industrial banks should prioritize digital transformation investments and provide comprehensive training programs to accountants and auditors, enabling them to leverage advanced technologies for improved financial reporting accuracy, operational efficiency, and competitive advantage.Keywords : Digital Transformation, Accounting Automation, Industrial Banking, Financial Technology, Iraqi Banking SectorHighlight : Digital transformation increases accounting automation efficiency by 86.9% in industrial banks. Strong positive correlation (0.932) exists between digitalization and automated financial processes. Modern technologies eliminate manual procedures, reducing costs and improving decision-making speed.